Covid-19 Pandemic amid Naira Devaluation - Umoru, David (Acta Universitatis Danubius. Œconomica, 2023)
In this paper, the COVID -19 induced socio-economic hardship in Nigeria was appraised in the face of Naira devaluation and the need for a living wage rate was advocated. The appraisal shows that the COVID-19 pandemic had deleterious effects on the Nigerian economy. By occasioning a plunge in oil price by 25%, the COVID-19 plague induced a government resolves on lockdown of over 200 million Nigerians whose per capita income was previously as low as $2,396.3, together with the embargo on interstate journeys, to quarantine the contagious impact of the pandemic, the Nigerian economy had to suffer negative growth rates of -6.10% and -2.48% for both Q2 and Q3 of 2020 in that order. And so, the Nigerian economy contracted easily resulting in an outcome of economic recession. Many Nigerians are presently more financially poor, and financially distressed and so wallow in hunger and socioeconomic hardship as exacerbated by the recent COVID-19 contagion. This has made the living cost excessively high and so becoming more difficult to live beyond poverty with a meager minimum wage of ₦30,000. Even when expenses are higher in Nigeria, salary levels have not been structured to make provision for income re-distribution so that people can afford to live in Nigeria. Hence, we advocate for a living wage of at least ₦312,928 per month which translates to a dollar equivalence of $680.28 per month for a full-time worker to cushion the negative effect of COVID-19 pandemic as it exceeds the poverty headcount amount.